Looking into the black box of “Medical Innovation”: rising health expenditures by illness type - Friedrich Breyer; Normann Lorenz; Gerald J. Pruckner; Thomas Schober (The European Journal of Health Economics, 2022)
There is agreement among health economists that on the whole medical innovation causes health care expenditures (HCE) to rise. This paper analyzes for which diagnoses HCE per patient have grown significantly faster than average HCE. We distinguish decedents (patients in their last 4 years of life) from survivors and use a unique dataset comprising detailed HCE of all members of a regional health insurance fund in Upper Austria for the period 2005–2018. Our results indicate that among decedents in particular, the expenditures for treatment of neoplasms have exceeded the general trend in HCE. This confirms that medical innovation for this group of diseases has been particularly strong over the last 15 years. For survivors, we find a noticeable growth in cases and cost per case for pregnancies and childbirth, and also for treatment of mental and behavioral disorders. We discuss whether these findings contradict the widespread interpretation of cost-increasing innovations as "medical progress" and offer some policy recommendations.
Keywords: H51; J11; I19; 610; Health care expenditures; Medical innovation; Cost of dying